Primary Health Care Technicians in the learning processes - Huerta Cruz, Alexandra Cecibel; Garcés Silva, Rita Elena; Estrella Acencio, Lidia Patricia; Heras Cordero, Alba Isabel (Revista Minerva, 2023)
Ecuador and other Latin American countries and the world are in an unfavorable position with respect to reading, inviting reflection on the problems that affect all levels of schooling, including higher education. In this line, the objective of the study was to analyze, through information obtained from reliable sources, the importance of reading as a competence in those university students who are professionally preparing to be early childhood teachers, considering that they will be the ones who contribute their knowledge to those children who will be your students in the very near future. The research is of a bibliographic, descriptive, non-experimental type, it is based on the value provided by the theories implicit in reading, the contribution of Paulo Freire’s critical pedagogy, which intends for students to come to reflection, questioning. The research has made it possible to know that it is extremely important that future professionals in initial education develop reading competence as an essential pillar of their professional training, concluding that higher education must provide motivational techniques or strategies to improve existing problems.